Perlindungan Hukum bagi Pemegang Saham yang Berasal dari Keputusan Rapat Umum Pemegang Saham (Studi Kasus Putusan Mahkamah Agung Nomor 4812 K/Pdt/2024) - Teuku Muhammad Rizky; Astim Riyanto; Endra Wijaya (Jurnal Hukum Lex Generalis, 2025)
Given the importance of the role of notaries in ensuring legal certainty and order through the preparation of authentic Actes, the author considers it necessary to examine in depth the aspects of legal responsibility attached to the position of notary. In particular, the author's attention is focused on the issue of notary responsibility in the issuance of Actes that later become the subject of legal disputes, such as in cases of default on the transfer of shares. This research falls under the category of normative legal research, also often known as doctrinal legal research. This approach views law as a set of norms that apply in society within the framework of the national legal system, and focuses on the study of legislation and other legal materials as the main sources of analysis. Due to its nature, which is not directly related to empirical objects, this research is also referred to as library research or document study, given that the data sources used come from studies of legal documents and scientific literature, and are secondary data. Supreme Court Decision Number 4812 K/Pdt/2024 shows that an authentic Acte, which should have full probative force, can be annulled by the court if there was negligence on the part of the notary in the process of its creation, particularly in ensuring that the formal requirements for holding a GMS were met. In this case, the Acte of GMS Decision was declared invalid because it was drawn up without the presence or power of attorney of the majority shareholders, which should have been the basis for the validity of a GMS decision. The notary's negligence in verifying the validity of the meeting caused the Acte to lose its authenticity and harmed the legitimate shareholders.